Phytochemical Constituents and Therapeutic Potential of Indian Medicinal Plants: A Comprehensive Review - Sharma, Shashank (Journal of Pharmacy Practice and Community Medicine)
The use of various traditional medicines like Unani, Siddha and Ayurveda has been practiced by indigenous cultures over time to treat health concerns. Traditional knowledge of using plants to heal is well-documented throughout India through numerous texts of Indian Medicinal Plants, providing valuable information about the use of plants for medicinal purposes. The traditional knowledge of the medicinal properties of Indian medicinal plants can also be applied utilizing phytoplasmic groups to help facilitate the healing process or promote the health of the patient being treated. The Phytoplasm Groups of Indian Medicinal Plants were classified into six distinct categories; alkaloids, flavonoids, terpenes, saponins, glycosides and phenolic compounds. The separate pharmacological properties of each phytoplasmic group used in traditional medicine are beneficial in their own right and provide numerous health benefits. This review’s objective is to list and describe the different Phytoplasm Groups found in Indian medicinal plants along with their pharmacological properties. Additionally, the pharmacological applications of phytoplasm from Indian medicinal plants include antioxidant activity, anti-inflammatory properties, antimicrobial activity, Antidiabetic properties, Anticancer activities, hepatoprotective activity and neuroprotective activity. Furthermore, the potential therapeutic uses of phytoplasm are based on the scientific validation of phytoplasm from Indian medicinal plants and therefore the development of new phytoplasm derived medicines should be based on the scientific validation of Indian medicinal plants to provide users with the maximum therapeutic benefits possible and utilize high-quality phytoplasm. The methodology was the main reason for the content of this review.
Keywords: Bioactive Phytoconstituents; Herbal Therapeutics; Indian Medicinal Plants; Pharmacological Activities; Phytochemical Groups; Traditional Medicine Systems